The role of management information systems in organizational decision making: A Review of the Literature - Khairina Eka Setyaputri; Muhamad Rosidin (Institute of Computer Science (IOCS), 2026)
This study explores the role of Management Information Systems (MIS) in enhancing the quality of organizational decision making through a systematic literature review of publications from the 2021–2025 period. A narrative literature review method was employed by analyzing 17 empirical studies retrieved from international academic databases, including Scopus, Google Scholar, and ScienceDirect. Thematic analysis identified three fundamental dimensions influencing the effectiveness of information systems in supporting organizational decision making: the technological dimension, characterized by the integration of artificial intelligence and machine learning; the organizational dimension, involving structural alignment and data driven culture; and the individual dimension, related to user competencies and algorithm aversion. The findings reveal that the implementation of Management Information Systems significantly improves decision accuracy by up to 82%, timeliness by 88%, and operational efficiency by 84%, with usage intensity, user competence, data quality, and system integration collectively explaining 58% of the variance in decision quality. Nevertheless, system effectiveness is constrained by inadequate user training, poor data quality, legacy system integration issues, low trust in algorithmic outputs, and organizational resistance to change. This study confirms that the benefits of Management Information Systems are not technologically deterministic; rather, they depend on a socio technical approach that integrates strategic alignment, digital capability investment, the development of a supportive organizational culture, and robust data governance to transform data into actionable business intelligence within strategic, tactical, and operational decision making contexts